2010
DOI: 10.3390/ijms11010067
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic and Antioxidant Effects of Dandelion (Taraxacum officinale) Root and Leaf on Cholesterol-Fed Rabbits

Abstract: Dandelion (Taraxacum officinale), an oriental herbal medicine, has been shown to favorably affect choleretic, antirheumatic and diuretin properties. Recent reports have indicated that excessive oxidative stress contributes to the development of atherosclerosis-linked metabolic syndrome. The objective of this current study was to investigate the possible hypolipidemic and antioxidative effects of dandelion root and leaf in rabbits fed with a high-cholesterol diet. A group of twenty eight male rabbits was divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
86
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(100 citation statements)
references
References 29 publications
11
86
0
3
Order By: Relevance
“…No negative effects were reported during pregnancy or lactation (Yarnell & Abascal 2009) Anticancer (Sigstedt et al 2008), antidiabetic (Yarnell & Abascal 2009), antifibrotic (Domitrović et al 2010), antioxidative and antiinflammatory activities (González-Castejón et al 2012;San et al 2014); hepatoprotective (Hfaiedh et al 2014), antimicrobial , antifungal (Astafieva et al 2013), antiviral (Han et al 2011) and antidepressant ) effects were reported of T. officinale. Reduction of adipogenesis and lipid accumulation in adipocytes (González-Castejón et al 2014) with hypolipidemic effects in cholesterol fed rabbits (Choi et al 2010) via pancreatic lipase and alpha glucosidase inhibitory activity (Onal et al 2005;Zhang et al 2008) were recognised for T. officinale.…”
Section: Herbal Remedies Of Fertility Pregnancy-related Issues and mentioning
confidence: 99%
“…No negative effects were reported during pregnancy or lactation (Yarnell & Abascal 2009) Anticancer (Sigstedt et al 2008), antidiabetic (Yarnell & Abascal 2009), antifibrotic (Domitrović et al 2010), antioxidative and antiinflammatory activities (González-Castejón et al 2012;San et al 2014); hepatoprotective (Hfaiedh et al 2014), antimicrobial , antifungal (Astafieva et al 2013), antiviral (Han et al 2011) and antidepressant ) effects were reported of T. officinale. Reduction of adipogenesis and lipid accumulation in adipocytes (González-Castejón et al 2014) with hypolipidemic effects in cholesterol fed rabbits (Choi et al 2010) via pancreatic lipase and alpha glucosidase inhibitory activity (Onal et al 2005;Zhang et al 2008) were recognised for T. officinale.…”
Section: Herbal Remedies Of Fertility Pregnancy-related Issues and mentioning
confidence: 99%
“…Wykazano, że duże spożycie produktów bogatych w cholesterol powoduje stłuszczenie wą-troby oraz sprzyja rozwojowi choroby wieńcowej i miażdżycy (Choi i in., 2010). W skutecznej walce z tymi chorobami może pomóc mniszek.…”
Section: Właściwości Hipolipidemiczneunclassified
“…Although, these metabolites do not have any crucial role in the growth and development, but actively participate in the adaptation, survival and acclimatization of plants to the external environment and represent unique source of naturally occurring phytochemicals 1 . Selection of high yielding productive cells and media formulations resulted in biosynthesis of important metabolites [2][3][4] . To meet out the demand of plant derived novel products in herbal market, plant tissue culture has been well recognized as a reliable and sustainable source for consistent production of raw material.…”
Section: Introductionmentioning
confidence: 99%